Shake It Off: Investigating the Function of a Domestic Dog Behavior in Social Contexts - Ani Bryce; Paige Nurkin; Alexandra Horowitz (Animals)
Shaking in domestic dogs—a rapid side-to-side movement of the body or head—is a commonly observed behavior, yet its function remains minimally researched. The present study aimed to investigate the use of shaking behavior in naturalistic social contexts, with the hypothesis that shaking functions as a marker of transition between behaviors or activities. In addition, as the prior literature has suggested that shaking more frequently occurred in postures or conditions of stress, either to signal stress or to mitigate it, we looked at postures related to affect before and after shaking. We observed 96 New York City dogs in two contexts: a public dog run and a private daycare. Over 120 episodes, shaking behavior was most often observed between two different activities or behavioral categories, supporting the hypothesis that shaking functions as a marker of transition between behaviors and activities. We also found neither a significant change in postures related to affect nor in the number of dogs in the subject’s vicinity after shaking. While there may be other functions of canine shaking behavior, this observational research adds to our understanding of a common and understudied dog behavior.